2021
DOI: 10.1029/2021jg006305
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Methane Emission From Global Reservoirs

Abstract: Methane (CH 4 ) is a potent greenhouse gas and its atmospheric concentration has increased significantly since the pre-industrial era and contributes to ∼20% of present-day observed global warming (Ciais et al., 2013). Anthropogenic activities (e.g., fossil fuel use and production, waste disposal, and agriculture) emit around 350 Tg CH 4 yr −1 (Saunois et al., 2016) and are assumed to be the primary contributors to increases in atmospheric CH 4 concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 102 publications
4
58
2
Order By: Relevance
“…We constructed a new freshwater estimate of 79 Tg CH 4 yr −1 consisting of 27 Tg CH 4 yr −1 from rivers (Stanley et al., 2016) quoted in Saunois et al. (2020), 10 Tg CH 4 yr −1 from reservoirs (Johnson et al., 2021), and our new lake estimate of 42 Tg CH 4 yr −1 . This revised freshwater aquatic emission estimate reduces the Saunois et al.…”
Section: Comparison With Other Lake Ch4 Emission Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a new freshwater estimate of 79 Tg CH 4 yr −1 consisting of 27 Tg CH 4 yr −1 from rivers (Stanley et al., 2016) quoted in Saunois et al. (2020), 10 Tg CH 4 yr −1 from reservoirs (Johnson et al., 2021), and our new lake estimate of 42 Tg CH 4 yr −1 . This revised freshwater aquatic emission estimate reduces the Saunois et al.…”
Section: Comparison With Other Lake Ch4 Emission Estimatesmentioning
confidence: 99%
“…Where multiple flux observations were reported as single averages, we expanded the compilation to reflect each observation when possible (i.e., when individual observations were reported). Subsequently, data were filtered to exclude indirect measurements (i.e., acoustic methods) and those lacking the necessary information on the time of day and month of year of observation and flux pathway (i.e., diffusive or ebullitive) (Johnson et al, 2021). For the boreal lake data provided in Wik et al (2016) we removed systems identified as Beaver Ponds.…”
Section: Flux Compilation Augmentation Correctionmentioning
confidence: 99%
“…emissions generally increase at lower latitudes (Barros et al, 2011), though more recent global syntheses with a similar spatial sampling bias reported no statistical difference between CH 4 emissions from tropical/subtropical vs. temperate reservoirs (Deemer et al, 2016;Johnson et al, 2021). One unique pathway by which CO 2 and CH 4 are emitted from many reservoirs is degassing (i.e., via turbines or spillways), which can account for over 50% of CH 4 emissions from reservoirs globally (Figure 3) (Harrison et al, 2021).…”
Section: Influence Of Inland Waterbody Types On Relative C Fluxesmentioning
confidence: 98%
“…This high productivity is associated with both a greater amount of autochthonous C preferred for CH 4 production (West et al, 2012) and low oxygen conditions following decomposition that promote CH 4 production. Research focused on CH 4 emissions from tropical reservoirs may bias these patterns as CH 4 emissions generally increase at lower latitudes (Barros et al, 2011), though more recent global syntheses with a similar spatial sampling bias reported no statistical difference between CH 4 emissions from tropical/subtropical vs. temperate reservoirs (Deemer et al, 2016; Johnson et al, 2021). One unique pathway by which CO 2 and CH 4 are emitted from many reservoirs is degassing (i.e., via turbines or spillways), which can account for over 50% of CH 4 emissions from reservoirs globally (Figure 3) (Harrison et al, 2021).…”
Section: Global C Fluxes In Inland Watersmentioning
confidence: 99%
“…Freshwater ecosystems emit large quantities of CH 4 to the atmosphere (currently estimated between 117 and 212 Tg CH 4 yr −1 ; Saunois et al, 2020). Within human-made reservoirs alone, ebullition rates can vary substantially in emissions, ranging from 1 to 1,000 mg CH 4 m −2 d −1 (Deemer et al, 2016) and up to 8.9 Tg CH 4 yr −1 (Johnson et al, 2021). Among the different types of freshwater CH 4 emissions, ebullition can make up anywhere from 0 to 99.6% of total emissions to the atmosphere (Deemer and Holgerson, 2021) and it is considered one of the most uncertain fluxes in both inland water and global CH 4 budgets (Wik et al, 2016;Saunois et al, 2020).…”
Section: Introductionmentioning
confidence: 99%